Sensibilidade de isolados de colletotrichum truncatum da soja a fungicidas - Silva, Bruna dos Santos da (2018)
Soybean anthracnose, caused by the fungus Colletotrichum truncatum, is one of the diseases that reduce crop yield. The difficulty to control the disease in some regions can be attributed to the reduction of fungus sensitivity to fungicides. The objectives of this research were to determine in vitro the fungitoxicity of different mechanisms of action, pure or in mixture, to isolates of C. truncatum, from different soybean producing regions of the country. The fungitoxicity of active ingredients was quantified by comparing the IC50 data from fungus isolates analyzed by three regression methods, with computational programs. Two experiments were carried out: the first determining in vitro the fungitoxicity of fungicides to the fungus isolates, using two isolates and 26 fungicides (Chapter I). The second was the in vitro sensitivity determination of 28 fungus isolates to six fungicides (Chapter II). Chapter III reports the IC50 calculation with different computational programs from the data collected in experiment I. The experiments were carried out in a completely randomized experimental design, designing bifactorial type treatments in four replicates. The methodology used was the same for both experiments, with five final concentrations of active ingredient: 0.01; 0.1; 1.0; 10 and 40 mg / L to determine fungitoxicity (I) and 0.1; 1.0; 10, 40 and 100 mg / L to determine the sensitivity (II). In the experiment I, the CT6 isolate presented the highest IC50 for benzimidazole (STI) and smaller for the multisite, while for CT21 the largest was for strobilurin (QoI) and the lowest for benzimidazole (STI). There was variability between the IC50 for the two isolates, indicating that their origin showed differences in the fungus sensitivity. For experiment II the active ingredient mixture azoxystrobin + benzovindiflupir was the one with the lowest IC50, while the mancozeb showed the highest. According to the region, Bahia and Mato Grosso presented the smallest IC50 and isolates without identification, from Rio Grande do Sul, the highest. The sensitivity of the fungus varies according to the origin, active ingredient and mechanisms of action. The fu ngus control will change according to the environment and fungicide. For Chapter III, the three statistical programs Microsoft Excel, RStudio and Infostat can beused for IC50 calculation, but for isolates with low sensitivity the value determined by the RStudio program showed better performance. The Microsoft Excel and Infostat programs tended to determine higher IC50 values than RStudio. Monitoring the fungus sensitivity should be performed to guide disease control in fungus populations and identify the best chemical control option.